The colors of the 25th April in Children’s literature 40 years after the Revolution - Ramos, Ana Margarida (2014)
It’s our purpose, in this study, to upgrade and actualize previous analysis of the depiction of the Portuguese April Revolution of 1974 in the editorial production aimed at children. The celebration of the 40 years of the most significant historical event of the twentieth century in Portugal explains the increase of various editions and reprints that complete a wide corpus of fictional and non-fictional texts, contemplating different goals and readings.